Bulgaria Financial Sector Assessment Program : Corporate Governance Review of the Banking Sector - World Bank Group (World Bank, Washington, DC, 2017)
This Review was prepared at the request of the Bulgaria National Bank (BNB). It presents the setting and the circumstances for the development of governance policies and practices in the Bulgarian banking system and reviews the effect of existing governance policy and practices on the oversight of banking sector related risks and prudential supervision. The objective of this Review is to help strengthen the corporate governance practices of banks in Bulgaria. Specifically, itintends to: further legal and regulatory reforms in Bulgaria based on the enclosed recommendations; enable the BNB to increasingly rely on the relevant internal and reportingsystems in those banks that have demonstrated better management and controls, therefore allowing supervisory resources to be directed toward troubled institutions and where needed the most; and promote corporate governance reforms in individual institutions, thereby enhancing the soundness of a specific bank. The Review focuses on the overall banking sector. The scope of the Review includes reviews of the: (i) legal and regulatory framework, (ii) corporate governance practices of banks, and (iii) enforcement framework vis-à-vis a set of benchmarks based on internationally recognized good practices in bank governance; a set of policy recommendations for the BNB on how to improve upon corporate governance in Bulgaria; and an action plan on how to implement theReview’s policy recommendations and effect reforms.